Analisis Indikator Ketenagakerjaan dan Demografi terhadap Kemiskinan di Jawa Barat - Tete Saepudin; Sestri Nurfala (Jurnal Riset Ilmu Ekonomi, 2022)
This study aims to examine and analyze the impact of population growth, the Human Development Index (HDI), underemployment, agricultural and non-agricultural workers on the number of poor people in West Java during the 2011-2019 period. This study is a quantitative and descriptive analysis, data collection techniques using secondary data obtained from the Central Bureau of Statistics of West Java, the Center for Employment Information Data and the National Development Planning Agency. The research subjects were 27 districts and cities with data analysis techniques using panel data regression. The results show that population growth has a positive effect on the number of poor people, the Human Development Index (HDI) has a negative impact on the number of poor people, and the underemployed population has a positive impact on the number of poor people. The large number of poor people and workers in the agricultural sector have a negative impact on the number of poor people, and employment in the non-agricultural sector has a negative impact on the number of poor people. Through this study it was found that population growth, Human Development Index (HDI), underemployed population, agricultural sector workers and non-agricultural sector workers as independent variables can explain changes in the number of poor people in West Java.